Analisis SWOT dalam Meningkatkan Daya Saing pada Perusahaan Fashion Dust - Sumaeda Sumaeda; Ustadus Sholihin; Beny Mahyudi Saputra (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to determine the SWOT analysis in increasing competitiveness at PT. Matahari Department Store Kediri. The problem in this study is "does SWOT Analysis play a role in increasing competitiveness at PT. Matahari Department Store Kediri. The research method used is the descriptive analysis research method, SWOT Matrix, External Factor Evaluation Matrix (EFE Matrix), Internal Factor Evaluation Matrix (IFE Matrix). The results of the study indicate that when PT. Matahari Department Store Kediri The competitive strategy implemented by PT. Matahari Department Store Kediri only provides quality products at affordable prices but also considers maximum product sales through social media, and maintains the company's image in the eyes of consumers so as to increase customer loyalty and the weighted value of the Internal Factor Evaluation Matrix (IFE Matrix) is 2.85 which indicates that the position of PT. Matahari Department Store Kediri has a very strong internal position. While the weighted value of the External Factor Evaluation Matrix (EFE Matrix) is 3.02 which indicates that PT. Matahari Departement Store Kediri in facing the dynamics of the external environment the company's position is relatively strong.